A politico-economic perspective on financial sustainability. Issue 1 (1st March 2014) - Slembeck, Tilman; Jans, Armin; Leu, Thomas
Abstract : Financial sustainability requires governments to run sufficiently large primary surpluses going forward to cover the cost of servicing its debt budgets to balance in the long run. In democracies, politicians who strive for reelection often tend to systematically violate this tenet. This paper discusses two types of "anchors" that may be used to cope with this problem by limiting the room for new and excessive public debt. First, we analyze national constitutional safeguards on the basis of the "debt brake" in Switzerland and Germany. Second, we discuss international institutions to maintain financial discipline, referring to the Maastricht-criteria. These anchors are designed to allow policymakers to commit to policies that provide long term financial stability and sustainability of public finances. However, as the recent crises have shown, the problem of time inconsistency in policy making remains, especially when anchors are weak. Therefore, the paper discusses the circumstances under which institutional anchors may help to restrict politician behavior to promote sustainability of public finances. We conclude by indentifying three conditions required for the proper functioning of collective anchors in the context of public finances.